Pemetaan Bibliometrik Menggunakan VOSviewer Terhadap Perkembangan Hasil Penelitian Literasi Informasi Pada Jurnal Perpustakaan di Indonesia - Thamrin Hasan; Mohamad Djaenudin (Perpustakaan Universitas Riau, 2023)
A bibliometric mapping study was carried out using VOSviewer on the development of information literacy research results in library journals in Indonesia. The development of information literacy research results published in library science journals and contained in databases that provide free access such as Google Scholar needs to be studied. This research aims to map the development of research results related to information literacy published by library science journals in Indonesia. The research was conducted in September-October 2023 by searching the Google Scholar database, using the keyword information literacy. The search result data was analyzed descriptively based on the year the publication was published, and the name of the institution that published the research results, the name of the journal/publication, and the type of document. To obtain a map of the development of this research, the data was exported in the Research Information Systems (ris*) file format. The export data is then processed and analyzed using the VOSiewer application to find a bibliometric map of the development of research results related to information literacy. The research results show that the development of research results related to information literacy topics indexed in the Google Scholar database found 142 research results within 5 years, with details in 2019 totaling 36 research results or 25.35%, in 2020 and 2021 respectively. each is amounting to 18 research results or 12.68%, and 23 research results, or 16.20%. In 2022 there were 34 research results or 23.94% and in 2023 based on data as of August 31 there were 31 research results or 21.83%. The conclusion of this study found that from 2019 to 2023, there were 142 indexed research results, and developments showed fluctuations, with the peak number of research in 2019.